I have to simplify (or get it in terms of tan I guess?) I'm not sure how to get the reference angle and subtract the angle 'x' from it to get an expressional value...how would I do this?
Follow Math Help Forum on Facebook and Google+
Originally Posted by daigo I have to simplify (or get it in terms of tan I guess?) I'm not sure how to get the reference angle and subtract the angle 'x' from it to get an expressional value...how would I do this? tan2pi/3==-root3 I'm writing t for tanx tan(2pi/3-x) = (-root3-t)/(1+root3*t) So cot (2pi/3-x) = (1+root3*t)/(-root3-t) = -(1+root3*t)/root3+t)
note the cofunction identity ... so ...
Got a sign wrong in my last reply. Should read tan(2pi/3-x)=(-root3-t)/(1-root3*t) So cot(2pi/3-x)=(1-root3*t)/(-root3-t)=-(1-root3*t)/(root3+t)= (root3*t-1)/(root3+t)
View Tag Cloud